Ukrainian Greek-Catholic Church (UGCC): Tourism and Environmental Activity in the Carpathians (30-ies of the XX century) - Olena Haydukevych (Cхід, 2016)
In this article we have analyzed some aspects of economic management of UGCC during 30-ies of XX century in the Carpathians, in particular, in the estate of Perehinsko: tourism and protection of nature. It has been proved that UGCC used to connect closely tourism activity with environmental protection as such combination of two areas of economic activity of the Church in complex social and political conditions of Halychyna of that time promoted formation of ecological and spiritual culture of the nation, consolidated the public opinion of the possibility of preservation of national identity of Halychyna people in future.